Modulation of cortical excitability can speed up blindsight but not improve it. - Cowey, A; Alexander, I; Ellison, A (2013)
Blindsight has been widely investigated and its properties documented. One property still debated and contested is the puzzling absence of phenomenal visual percepts of visual stimuli that can be detected with perfect accuracy. We investigated the possibility that phenomenal visual percepts of exogenous visual stimuli in patient GY might be induced by using transcranial direct current stimulation. High contrast and low contrast stimuli were presented as a moving grating in his blind hemifield. When left area MT/V5 was anodally stimulated during the presentation of high-contrast gratings, he never reported a phenomenal percept of a moving grating but showed perfect blindsight performance. When applied along with low contrast gratings, for which accuracy was titrated to 60-70 %, performance did not improve but responses were significantly faster. Cathodal stimulation had no effect. Results are explained in the framework of GY's reorganized cortical connexions and oscillatory patterns known to be involved in awareness in GY. The apparent presence of phenomenal visual percepts in earlier studies is shown to be a semantic confusion about what he means when he says that he sees in his blind field.